Analisis Media Sosial, Faktor Sosial, dan Psikologi Konsumen yang Mempengaruhi Partisipasi Konsumen dalam Boikot McDonald’s di Kota Semarang - Luky Indra Mustofa; Piji Pakarti; Mahmud; Amalia Nur Chasanah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of social media, social factors, and consumer psychology on the decision to participate in the boycott movement against McDonald’s (McD) products in Semarang City. A quantitative method was employed, utilizing purposive sampling to select 163 respondents who met the criteria: prior purchase of McD products, awareness of the boycott issue, active social media usage, Islamic religious affiliation, and residency in Semarang. Data were collected through Linkert-scale questionnaires and analyzed using multiple linear regression analysis with SPSS. The results indicate significant influences from all three factors: social media, social factors, and consumer psychology. The coefficient of determination reveals that 32% of the variation in boycott decisions is attributed to these factors. These findings underscore the critical integration of digital, social, and moral dimensions in understanding the dynamics of ideologically driven boycott movements. Practical implications include recommendations for companies to develop crisis communication strategies aligned with local values and consumer ethics to mitigate boycott impacts.